Rap sheets in criminological research: Considerations and caveats - Geerken, Michael R. (Journal of quantitative criminology, 1994)
The types of errors found in official criminal history records are not completely understood by many researchers, and this lack of understanding can lead to serious misinterpretations. Analyses of a recently developed database of New Orleans offenders indicate that the use of rap sheets with a limited catchment area can lead to gross distortions of the effects of variables related to geographic mobility, such as race and age. Evidence from a number of sources indicates that false-negative error is a serious problem, particularly in fingerprint-based record systems. In addition, arrest records lend themselves to a variety of common misinterpretations by researchers in the coding process, including failing to identify multievent arrests, misclassifying arrests, and treating arrest or custody process events as crimes indicating criminal activity of the individual while free. Solutions to some of these problems are suggested.